Argulosis causing juvenile mortality in some fishes at Kakdwip, West Bengal - Nandi, N C; Das, S R (Indian Journal of Fisheries, 2011)
Diseases and parasites of food fishes inIndia and adjacent countries were reported onseveral occasions (Gopalakrishnan 1967). Afew cases of argulosis associated with fishmortality were also known from Indian ponds(Hora 1943; Anonymous 1955,1960; Gopalakrishnan1963, 1964; Tripathi 1975). However,Ramakrishna (1951) reported the occurrenceof Argulus siamensis for the first timefrom India. He had examined Southwell's(1915) and Hora's (1943) collection and identifiedthem as A. siamensis. Afterwards areponofA. siamensis infecting large number offishes of a pond at Salkia, Howrah, appeared inthe Annual Report of the Central Marine FisheriesResearch Institute, Mandapam (Anonymous1955).